2010
DOI: 10.1007/s11916-010-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Olfactory Stimuli

Abstract: Migraine patients often report intolerance to odours. Migraineurs report odours may trigger attacks, that they experience osmophobia during attacks, and olfactory hypersensitivity between attacks. In this paper we discuss olfactory mechanisms in migraine. We also present data from a pilot questionnaire study in a group of young women diagnosed with migraine. The study results confirm that hypersensitivity to odour is a common feature in women with migraine. Migraine pathophysiology likely explains this particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
0
7

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(112 citation statements)
references
References 45 publications
(51 reference statements)
5
88
0
7
Order By: Relevance
“…We hypothesize that odorant substances bind to olfactory receptors and activate adenylate cyclase, leading to cyclic adenosine monophosphate (cAMP), which binds to sodium channels, triggering an action potential which propagates to the olfactory bulb [27]. These electrical impulses are directed to the primary olfactory cortex, where discrimination of odor happens [3,10]. Therefore, the action potential is not spread when the sodium channels are blocked by phenytoin and osmophobia is relieved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesize that odorant substances bind to olfactory receptors and activate adenylate cyclase, leading to cyclic adenosine monophosphate (cAMP), which binds to sodium channels, triggering an action potential which propagates to the olfactory bulb [27]. These electrical impulses are directed to the primary olfactory cortex, where discrimination of odor happens [3,10]. Therefore, the action potential is not spread when the sodium channels are blocked by phenytoin and osmophobia is relieved.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant association between odors and primary headaches, particularly to migraine with or without aura [1][2][3][4][5][6] and tension-type headache [1,[6][7][8]. The literature of its occurrence in secondary headaches is very scarce [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, we observed a severe intolerance to odours, pleasant or unpleasant, during headache attacks. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, a limited number of studies showed that odours may trigger headache attacks in some patients, particularly in migraineurs 1,3,6,7,9,24 and occasionally in cluster headache patients. 12,18 This intolerance to odours is known as osmophobia, and according to two studies that investigated osmophobia in secondary headaches, it occurred during headache attacks only in the primary headaches.…”
mentioning
confidence: 99%